Campinas, una villa colonial (1774-1822) - Teixeira, Paulo Eduardo [UNESP] (Associacao Brasileira de Estudos Populacionais, 2017)
The development of agriculture in São Paulo, Brazil, presented a significant expansion during the late eighteenth and early nineteenth centuries, which is the focus of this paper. The purpose is to understand the dynamics and movements of these populations of a region of plantations (slaveholding properties). The sources for this discussion are derived from the General Map of Inhabitants existing for the period 1798-1822 in Campinas, with added data from the Nominative Lists of inhabitants and Parish Registers. Despite evident data limitation, there was a strong demographic increase, especially in captive population.
Campinas, uma vila colonial (1774-1822)
Campinas, a colonial village (1774-1822)
Keywords: 18th century; Birth rate; Marriage rate; Mortality; Settlement; Slavery